The Impact of Employee Competence, Culture of Innovation, and Leadership Style on Organizational Effectiveness - Gideon Dian Permana; Okder Pendrian (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
One of the parameters in looking at the effectiveness of organization in a governmental system is that it can be seen through the achievement value of Bureaucratic Reform. Bureaucratic reform is a systematic, integrated and comprehensive effort to good governance. The study aims to test and analyze the impact of employee competence, culture of innovation, and leadership style on the effectiveness of organizations in the Coordinating Ministry for Human Development and Cultural Affairs Indonesia. The results of this study show that employee competence, culture of innovation, and leadership style have a positive impact on organizational effectiveness. It should be an organization’s concern to improve the quality of competence, culture of innovation, and style of leadership so that the effectiveness of the organization can be achieved optimally.